The Isolation and Identification of Lactobacillus from Naturally Fermented Yoghurt. Issue 1 (September 2020) - Wu, Ya; Wu, Dongdong; Liu, Danyan; Chen, Juling; Zhao, Xin
Abstract: Lactic acid bacteria were isolated from natural fermented yoghurt by traditional isolation and culture method, and identified by gram staining and 16S rDNA sequencing analysis. The results showed that 5 strains of lactic acid bacteria were obtained, which were X22-1, X22- 2, X22-3, X22-4 and X40-1. After 16S rDNA sequencing, X22-1, X22-3, X40-1 were Lactobacillus fermentans, X22-2 and X22-4 were Lactobacillus delbrueckii subsp. Bulgaricus.